HUBUNGAN METODE PEMBELAJARAN DISKUSI DENGAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS X IPS DI SMA NEGERI 1 MOTOLING - Crismi Sintia Mega Rambi; Abdul Rasyid Umaternate; Yoseph D.A Santie (Labor Program Studi Pendidikan Sosiologi, 2021)
The purpose of this study was to determine the relationship between the discussion learning method and the learning motivation of students in class X Social Studies in sociology at SMA Negeri 1 Motoling. This research is quantitative descriptive. In this study, the population used was 30 students of class X IPS at SMA Negeri 1 Motoling who were representatives of Class X IPS 1, X IPS 2, and X IPS 3. The instruments and data collection techniques used were questionnaires and documentation with analytical techniques. The data used are Product Moment validity and Cronbach Alpha reliability tests. The results of this study indicate that there is a ralationship between the discussion learning method and students learning motivation, this is evidenced by the coefficient of determination (R Square) of 0.589 which implies that the influence of the independet variable (X) on the dependent variable (Y) is 58.9% and the remaining 41.1% is imfluenced or determined by other factors.